An analytical model for evaluating the buckling, delamination propagation, and failure behaviors of delaminated composites under uniaxial compression. (1st September 2019) - Wang, Kangkang; Zhao, Libin; Hong, Haiming; Gong, Yu; Zhang, Jianyu; Hu, Ning
Abstract: Laminated carbon fibre reinforced composite materials are very susceptible to delamination, which is one of the most serious failure modes in composite laminates. According to the requests of damage tolerance evaluation, to completely evaluate the buckling responses and failure behaviors of delaminated composites under uniaxial compression, an analytical model was established. Based on the principle of minimum potential energy and brittle damage mechanics, the analytical model incorporated both the delamination propagation and failure evaluation into the buckling analysis. Uniaxial compression tests of three specimens containing embedded delaminations were conducted. The predicted results are highly consistent with the experimental outcomes, thus validating the applicability and accuracy of the proposed analytical model. It is found that the out-of-plane deflections and energy release rate of the delaminated laminate are closely related to the buckling states; the choice of G C in a range from G IC to G IIC has little effect on the predicted results with the proposed model.